Different dietary sources of selenium alter meat quality, shelf life, selenium deposition, and antioxidant status in Hu lambs. (December 2022) - Bai, Xue; Li, Fei; Li, Fadi; Guo, Long
Abstract: Thirty-two male Hu lambs (32.31 ± 3.31 kg; 4-months-old) were randomly assigned to four treatments: (1) control (CON), (2) selenium-enriched yeast (SeY, 0.8 mg/kg), (3) selenized glucose (SeGlu, 0.8 mg/kg), and (4) sodium selenite (SS, 0.8 mg/kg) to evaluate their effects on Hu lamb production and slaughter performance, antioxidant capacity, hematological parameters, meat quality and shelf-life. The production and slaughter performances were not different ( P > 0.05) among treatments. SeGlu and SeY increased ( P < 0.05) the total antioxidant capacity in serum and muscle selenium content while decreasing ( P < 0.05) the malondialdehyde (MDA) contents both in serum and muscle. SeGlu extended muscle shelf-life by 7.7 h compared with CON and decreased ( P < 0.05) yellowness (b*) and lightness (L*) in meat stored for 24 h. In summary, the effects of SeGlu were similar to those of SeY and better than those of SS in improving serum and muscle antioxidant status, prolonging muscle shelf-life, and increasing selenium deposition in muscle. Highlights: Sodium selenite, Se-yeast, and selenized glucose could raise serum antioxidant capacity and muscle Se content in lambs. A new organic selenium source, selenized glucose, can be used as a feed additive to produce selenium-enriched meat. Selenized glucose could improve the antioxidant capacity and prolong the shelf life of lamb meat.